2021
DOI: 10.1080/08897077.2021.1901174
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Need and Risk, Supply and Demand: Developing a Tool to Prioritize Naloxone Distribution

Abstract: Background: Opioid overdose deaths continue to rise nationally. The demand for naloxone, the opioid overdose antidote, is outpacing the supply. With increasing naloxone requests, tools to prioritize distribution are critical to ensure available supplies will reach those at highest risk of overdose. Methods: We developed a standardized "Naloxone Request Form" (NRF) and corresponding weighted prioritization algorithm to serve as decisional aid to better enable grant staff to prioritize naloxone distribution in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Our study findings are consistent with assessments by the American Society of Addiction Medicine, the CDC, and previous research studies that have recommended developing more effective naloxone distribution strategies to reach the highest-need locations and populations. An analysis by the CDC of naloxone dispensing showed that rural counties were more likely to be underserved, and a prior study also identified disparities in naloxone access between urban and nonurban regions in Rhode Island .…”
Section: Discussionmentioning
confidence: 93%
“…Our study findings are consistent with assessments by the American Society of Addiction Medicine, the CDC, and previous research studies that have recommended developing more effective naloxone distribution strategies to reach the highest-need locations and populations. An analysis by the CDC of naloxone dispensing showed that rural counties were more likely to be underserved, and a prior study also identified disparities in naloxone access between urban and nonurban regions in Rhode Island .…”
Section: Discussionmentioning
confidence: 93%